2018
DOI: 10.1080/14794802.2017.1410215
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between metacognitive and collaborative talk during group mathematical problem-solving – what do we mean bycollaborativemetacognition?

Abstract: The purpose of this study was to enhance our understanding of the relationship between collaborative talk and metacognitive talk during group mathematical problem-solving. Research suggests that collaborative talk may mediate the use of metacognitive talk, which in turn is associated with improved learning outcomes. However, our understanding of the role of group work on the individual use of metacognition during problem-solving has been limited because research has focused on either the individual or the grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 51 publications
1
36
0
2
Order By: Relevance
“…First, in mastery of mathematics concept and second is about student's thinking skills. Reviewed articles showed that implementation of metacognitive learning strategies by organizing certain activities likes Problem Based Learning, Project Work, Discussion, Game, etc, is mostly effective to students performance and understanding (e.g; Daher, Anabousy, & Jabarin, 2018;Smith & Mancy, 2018;Suriyon, Inprasitha, & Sangaroon, 2013). It means, student learning is greatly enhanced when the student's level of prior knowledge is made visible.…”
Section: What Is the Impact Of Learning Activities As The Interventiomentioning
confidence: 99%
See 3 more Smart Citations
“…First, in mastery of mathematics concept and second is about student's thinking skills. Reviewed articles showed that implementation of metacognitive learning strategies by organizing certain activities likes Problem Based Learning, Project Work, Discussion, Game, etc, is mostly effective to students performance and understanding (e.g; Daher, Anabousy, & Jabarin, 2018;Smith & Mancy, 2018;Suriyon, Inprasitha, & Sangaroon, 2013). It means, student learning is greatly enhanced when the student's level of prior knowledge is made visible.…”
Section: What Is the Impact Of Learning Activities As The Interventiomentioning
confidence: 99%
“…They can identify logical errors, and it can help students to solve the problems. If student can think critically, creatively, and solve mathematic problems independently, then they will be able to succeed in making decisions (Du Toit & Du Toit, 2013; Schraw & Moshman,1995), understand options and expand knowledge to daily life (Ackerman & Leiser, 2014;Smith & Mancy, 2018).…”
Section: What Is the Impact Of Learning Activities As The Interventiomentioning
confidence: 99%
See 2 more Smart Citations
“…According to Wood (2017), learning activities and processes that encourage active student engagement and can have optimal interaction effects should be considered when teachers are choosing teaching and learning approaches. According to Smith & Mancy (2018), when students interact during learning, the discussions between them focus heavily on metacognitive aspects, and this will lead to training for improving their metacognitive skills. According to Dagarin (2005) and Jose(2016) interactions are in many ways including, students-teachers, students-students, and even students-themselves.…”
Section: Introductionmentioning
confidence: 99%